INDICATORS OF HEPATOPULMONAINDICATORS OF HEPATOPULMONARY SYNDROME IN PATIENTS WITH PORTAL HYPERTENSION - Mushtaq, Iqra; Cheema, Huma Arshad; Malik, Hassan Suleman; Waheed, Nadia (Journal of Ayub Medical College Abbottabad, 2021)
Background: Hepatopulmonary syndrome is severe pulmonary vascular complication of chronic liver disease requiring liver transplant. This study was conducted to evaluate different indicators of HPS in patients with portal hypertension, its varied aetiologies, clinical features & outcome. Methods: Hospital based descriptive study, 203 patients were enrolled, divided in to 2 groups positive and negative on the basis of presence or absence of HPS as per diagnostic criteria. Results: It included 203 patients with portal Hypertension of varied aetiologies. Age range was 8.76±3.69 years. 54.7% were male & 45.3% female. Commonest diagnosis for portal hypertension was portal vein thrombosis in 48 (23.6%) while Least common was biliary atresia seen in 6 (3%) of cases. Fifteen patients were included in Positive group and 188 in negative group. Clinical & laboratory parameters in order of frequency in positive group were hypoxia & cyanosis in 100% & 93.3% followed by dyspnoea & grade 4 clubbing in 86.6% patients (p<0.001). Child scoring was also done in all patients. In negative group 7 (3.7%) had dyspnoea, I (0.53%) had grade 4 clubbing while none showed evidence of hypoxia or cyanosis (p<0.001). Three patients underwent a successful liver transplant. One patient of biliary atresia & another of CHF expired. Conclusion: In All children with CLD and/or PHT with unexplained dyspnoea, cyanosis and grade 4 clubbing, HPS should be suspected. It is an indication for early LT even in absence of liver failure. Keywords: Hepatopulmonary syndrome; Arterial oxygen tension; PaO2; Alveolar-arterial oxygen gradient O2 gradient; contrast-enhanced echocardiography; CEE; technetium-99m Macro aggregated Albumin; 99 mTc-MAA, Liver Transplant